The relative decline of interest in regional geography as a geographical study methodology compared with alternative methods - Mhlahlo, S. R. (Midlands State University, 2015)
The growing concern about the environment and sustainable development reveals the connections between human and physical branches of geography. The functional specialization of geographical enquiry into thematically focused fields reveals the construction of disciplinary knowledge. Such dismemberment of geographical study has resulted in a relative decline of interest in regional geography as a geographical study methodology in favour of alternative methods of enquiry. The discussion will define “region” and “regional geography,” and analyze the decline of interest in the regional concept since the mid-nineteenth century and examine the influence of industrial development to regional studies. The study critically examines the weakness of the regional geography concept that resulted in the relative decline of interest. Using secondary data, the research examines the geographical methodologies and approaches that replaced regional geography. The sample, quantitative and systematic studies, in the new geography are investigated. The investigation explores the advantages of regional geography and efforts to revive regional geography, owing to its intellectual vigour. The research concludes that alternative geographical study methodologies are not completely divorced from the regional concept.